PENYELIDIKAN SIFAT MEKANIS BAHAN KOMPOSIT POLIMER DIPERKUAT SERAT BATANG PISANG KEPOK AKIBAT BEBAN TARIK - mhd juliandi; Ade Irwan; Fadly A Kurniawan (Jurnal Simetri Rekayasa, 2020)
This study aims to determine the process of making composite fiber made from kepok bananas (Musa Acuminata) and to find out how much tensile test (Modulus of elasticity and Modulus of Rapture) composites of fibers made from kepok banana (Musa Acuminata). The study was conducted at the laboratory of the University of North Sumatra, the length of the tensile test object is 15 cm, thickness 0.5 cm and width 1 cm, in this study the writer got a maximum stress value of 32.06407 and a Maximum Load value of 1603,203